On the Pattern of Currency Blocs in Africa - Yehoue, Etienne (IMF Working Papers; Working Paper ;, 2005)
This paper seeks to elucidate the debate over currency union in Africa. The paper examines whether empirical investigation points to the gradual emergence of currency blocs. Based on the historical data on inflation, trade, and the comovements of prices and outputs, I argue that the emergence of large-scale currency blocs in Africa will follow a gradual path and that this dynamic does not lead to the emergence of a single continental currency at this time. Rather, the pattern which emerges seems to suggest three blocs: one in West Africa, a second around South Africa, and a third in Central Africa. Although little evidence is found supporting the emergence of a single African currency at this time, the emergence of an African currency union is not necessarily precluded, since the ultimate decision to surrender a nation's monetary policy to a supranational institution is not made based solely on economic considerations. I then address the issue of a possible anchor for the union, were it to emerge and opt for an anchorage. I find- based on the trade criterion-that the euro seems to be a good choice.